Simulation of power line communications channel using mathematical model - Chmielewska, Irena; Nawrot, Wojciech (Видавництво Національного університету «Львівська політехніка», 2003)
In the paper, the main factors degrading a telecommunication signal transmitted over the power grid wires are identified. A mathematical model of the PowerLineCommunication (PLC) channel reflecting signal multipath and attenuation is discussed. Simulation of a real PLC channel for broadband signals transmission carried out by the authors, based on the Dossert’s model, is described and the results (true LV distribution network transmission parameters, transfer function characteristic) are reported.